Deklarasi Al-Qur’an terhadap Budaya Literasi dan Urgensinya dalam Pembentukan Karakter (Kajian Q.S. Al-‘Alaq Ayat 1-5) - Nazil Mumtaz al-Mujtahid; Achyar Zein (Program Pascasarjana Universitas Islam Negeri Sumatera utara, 2022)
This study seeks to describe the Koranic statement on literacy culture and the importance of character development. This article discusses the contemporary issues of the Indonesian nation, specifically the low incidence of illiteracy. Ironically, low levels of illiteracy are not followed by high levels of literacy. The greatest contributor to Indonesia's low literacy rate is a lack of interest, according to data collected by the author. In fact, the Qur'an emphasizes the influence of literacy culture on character formation. In this article, the author focuses primarily on verses 1 through 5 of surah al-'Alaq. This article employs a qualitative methodology that is interpretive and social in orientation. The technique for collecting data is a literature review involving the examination of numerous scientific works with titles. This article employs content analysis to generate reliable information. The results of the study indicate, first, that Muslims are obligated by the Koran to cultivate a reading culture with a strong correlation to literacy. Second, surah al-Alaq has a substantial impact on character development, as the strength and weakness of a person's character is largely dependent on his or her literacy culture. Third, all of sura al-Alaq's messages can be used as a resource for character development.